Pattern of Thoraco-Abdominal Injuries in Fatal Road Traffic Accidents in Mangalore City - Abymon K K; Mohd Amjad Bhat; Azia Manzoor Bhat (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: After the strict implementation of helmet rule the number of head injuries due to road trafficaccidents has subsequently decreased, but injuries sustained to thoracic and abdominal regions are still on therise. Because of their size and anatomical position, they are major regions of trauma in road traffic accidents.This post mortem study of profile of thoraco-abdominal injuries, type, pattern and nature of external andinternal injuries involved, was an attempt to highlight the trends & pattern of thoraco-abdominal injuries infatal road traffic accidents in Mangalore city. Material and Methods: Present study was a retrospective,autopsy-record based study of thoraco-abdominal injuries sustained in fatal road traffic accidents. Detailsof deceased individuals such as age, sex, information furnished by the police in the inquest papers (form146 (i) & (ii)), autopsy findings, investigation reports if any and cause of death were noted in proforma.Results: During study period among 4271 cases 859 cases (20%) were due to road traffic accidents. Out ofthese 859 cases of road traffic accidents 247 cases (29%) sustained thoraco-abdominal injuries. 38.5% caseshappened on city roads & pedestrians were most common victims (45.8%). Most common injuries werefractures of ribs (60%), followed by injuries to lungs (37%) cases and injuries to heart (23%). Crush injurieswere observed in 6% of cases. There were 136 (55%) cases of internal abdominal injuries, most commonorgan injured was liver (38%), followed by spleen (17%) & abdominal wall (14%). Among the 247 cases,most common cause of death was head injury (47%) followed by thoraco- abdominal injury (20%), headinjury and thoracic injury (8%), only thoracic injury (7%), abdominal injury (6%). Conclusion: Most fatalaccidents were reported on city roads, in summer season and cause of death was head injury followed bythoraco-abdominal injuries. Ribs, lungs and Liver were the organs most commonly injured.